Quantitative comparison of the protein corona of nanoparticles with different matrices - Ilaria Ottonelli; Jason Thomas Duskey; Filippo Genovese; Francesca Pederzoli; Riccardo Caraffi; Marta Valenza; Giovanni Tosi; Maria Angela Vandelli; Barbara Ruozi (Elsevier, 2022)
Nanoparticles (NPs) are paving the way for improved treatments for difficult to treat diseases diseases; however, much is unknown about their fate in the body. One important factor is the interaction between NPs and blood proteins leading to the formation known as the "protein corona" (PC). The PC, consisting of the Hard (HC) and Soft Corona (SC), varies greatly based on the NP composition, size, and surface properties. This highlights the need for specific studies to differentiate the PC formation for each individual NP system. This work focused on comparing the HC and SC of three NPs with different matrix compositions: a) polymeric NPs based on poly(lactic-co-glycolic) acid (PLGA), b) hybrid NPs consisting of PLGA and Cholesterol, and c) lipidic NPs made only of Cholesterol. NPs were formulated and characterized for their physico-chemical characteristics and composition, and then were incubated in human plasma. In-depth purification, identification, and statistical analysis were then performed to identify the HC and SC components. Finally, similar investigations demonstrated whether the presence of a targeting ligand on the NP surface would affect the PC makeup. These results highlighted the different PC fingerprints of these NPs, which will be critical to better understand the biological influences of the PC and improve future NP designs.